The Hagarism at Patricia Crone and Michael Cook, A com- parative commentary study between Western Christian thought and facts of Islam - Dhahi Al-Dulaimi, Muhammad Abed (Opción, 2019)
The research included a comparative commentary study between Western Chris- tian thought and facts of Islam by the book of historians Patricia Crone and Mi- chael Cook: (Hagarism: The Making of the Islamic World) it is on the early history of the religion of Islam, in which the authors gave a different conception of Islam based primarily on Judaism and Christianity and excluding Islamic sources and relying instead on non-Islamic sources in a failed attempt to obliterate Islamic his- tory and invent a new history that agrees with their ideology. The study indicates the lack of objectivity of the researchers in their selection of these sources, because they are highly questionable due to the inaccuracy of the transfer of information and the intertwined and the many questions that revolve around some of the names that came in their book, contrary to the traditional Islamic historical perception contained in our Islamic books, as researchers are trying in their work (Hagarism) and in other works questioning the Muslim thoughts, including the name of Islam. They said that there is no evidence of the designation of Islam in the time of the Prophet Muhammad (Peace be upon him), This name appeared for the first time in 691 AD, but the emergence of the original manuscripts of the messages of the Prophet Muhammad (Peace be upon him) to some Kings especially to the king Amuqawqas, which was recently found in a monastery in Egypt, carried the name of Islam and it refuted authors allegations and showed the weakness of the sources that they have adopted in their claims.